Danny, the Champion of the World (Knopf : distributed by Random House, J. Cape, s.n, Bantam Books, KNOPF, Books on Tape, Puffin Books, Puffin, Penguin Young Readers Group, 1975)
Danny is brought up by his father, who's a great storyteller and a genius with cars and kites. He's also a poacher, and with Danny's help he catches more pheasants than anyone else in the history of poaching.

Seashore (Usborne young beginners, ,, 2017)
Seashore is part of an informative and exciting new series for children aged three and up, with simple text that children can easily understand. Topics are chosen for their appeal to the very young, to answer endless questions and inspire new ones! Other topics in the series are Flowers, Bugs, Baby Animals and Woodland Creatures. Filled with beautiful illustrations, this is an essential addition to any family bookshelf.

Music (Eyewitness books, , 1, 2004)
Describes some of the many different types of instruments made throughout history, and discusses their construction and sound. Includes photographs.
Seeing sound , Wind tunnels , Pipes and flutes , Vibrating reeds , Long-lasting hybrids , Bags of sound , Piped music , Beginning of brass , Blazing brass , Curly horns and big tubas , Breaking the silence , Early and unusual strings , Violin family , Making a violin , Harps and lyres , From pears to whole fishes , From gourd to board , Indian string , Creating a guitar , Keynotes , Grand and upright , Musical impact , Rhythm and ritual , On the beat , Appeal of percussion , Clang, crash, bang , Electrifying music , Rock guitars , Machine music.

The story of Ferdinand (Reading Beyond the Basal, ,, 1987)
Ferdinand the bull likes to sit quietly and smell the flowers, but one day he gets stung by a bee and his snorting and stomping convince everyone that he is the fiercest of bulls. Includes read-along disc in English or Spanish.

Giraffes can't dance (Scholastic Inc, Orchard Books, Scholastic, 2001)
Gerald the giraffe is too clumsy to dance with all the other animals at the Jungle Dance, until he finds the right music.

Dog (Eyewitness books, , 1, 2004)
Text and photographs highlight the evolutionary history of dogs, their domestication, anatomy, behavior, and breeds, and offer guidance on dog care and training.--
What is a dog? , Dog family evolution , Dogs' bones , Coats, heads, tails , Sight, sound , On the scent , Behavior , Puppies , Pack leader , Jackals , African-Asian dogs , Red or gray? , Hot and cold foxes , Foxy zorro , Domestication , Feral dogs , Breeding dogs , Hunting dogs , Herding dogs , Helper dogs , Sport dogs , Hounds , Sporting , Terriers , Utility dogs , Working dogs , Toy dogs , Crossbred dogs , Dog care , Did you know? , Identifying dogs.

One Fish, Two Fish, Red Fish, Blue Fish (I can read it all by myself beginner books, ,, 2005)
A crazy story in verse in which a series of unusually-named creatures (some of which are fish)--Nook, Womp, Yink, Yap, Gack and the Zeds--run into equally-zany situations. Fabulously easy words, exciting pictures, and inviting rhythm!
Track 1. Read-along (10:26) , Track 2. Storytelling (9:00).

Who was Albert Einstein? (Who was-- ?, , 1, 2018)
Recounts the life of the scientist whose theories of relativity revolutionized the way we look at space and time.
Born to Think , What's to Be Done with a Genius? , Albert Takes a Very Deep Breath ... and Keeps Thinking , The Best Years , Albert Hits High Gear , War ... Again , Albert's Time Is Up , A Final Thought.

The gruffalo (Puffin, Scholastic Inc, Dial Books for Young Readers, Penguin Young Readers Group, 2006)
A mouse is taking a stroll through the deep, dark wood when along comes a hungry fox, then an owl, and then a snake. The mouse is good enough to eat but smart enough to know this, so he invents ... the gruffalo! As Mouse explains, the gruffalo is a creature with terrible claws, and terrible tusks in its terrible jaws, and knobbly knees and turned-out toes, and a poisonous wart at the end of its nose. But Mouse has no worry to show. After all, there s no such thing as a gruffalo.

Player piano (Delacorte Press, Dell Publishing, RosettaBooks, 1952)
Vonnegut's first novel spins the chilling tale of engineer Paul Proteus, who must find a way to live in a world dominated by a super computer and run completely by machines. His rebellion is a wildly funny, darkly satirical look at modern society. This novel, an unforgiving portrait of an automated and totalitarian future, was published in 1952. A human revolt against the machines which control life was arranged by the machines themselves to prove the futility of such resistance. Visionary and unrelenting, this is felt by some critics to be Vonnegut's best and most original novel.

Djibouti (William Morrow, Harper Collins Publishers, Blackstone Audio, Inc., HarperCollins, HarperAudio, HarperCollins Publishers, 2010)
In a modern-day pirate story, ambitious documentary filmmaker Dara Barr and her right-hand man, Xavier LeBo, a seventy-two-year-old African American seafarer, get more than they bargained for on the Horn of Africa.

The story of mankind (LIVERIGHT, Good Press, Liveright, 2019)
This classic history, first published in 1921 and winner of the first Newbery Medal, was illustrated in pen and ink by the author. This version has incorporated recent events to make it an up-to-date world history.
The setting of the stage , Our earliest ancestors , Prehistoric man , Hieroglyphics , The Nile Valley , The story of Egypt , Mesopotamia , The Sumerians , Moses , The Phoenicians , The Indo-Europeans , The Aegean Sea , The Greeks , The Greek cities , Greek self-government , Greek life , The Greek theatre , The Persian wars , Athens vs. Sparta , Alexander the Great , A summary , Rome and Carthage , The rise of Rome , The Roman Empire , Joshua of Nazareth , The fall of Rome , Rise of the church , Mohammed , Charlemagne , The norsemen , Feudalism , Chivalry , Pope vs. Emperor , The Crusades , The Mediaeval City , Mediaeval self-government , The Mediaeval world , Mediaeval trade , The Renaissance , The age of expresssion , The great discoveries , Buddha and Confucius , The Reformation , Religious warfare , The English Revolution , The balance of power , The rise of Russia , Russia vs. Sweden , The rise of Prussia , The mercantile system , The American Revolution , The French Revolution , Napoleon , The Holy Alliance , The great reaction , National independence , The age of the engine , The social revolution , Emancipation , The age of science , Art , Colonial expansion and war , A new world , As it ever shall be , After seven years , The United States comes of age , The "axis" partners , Isolationism and appeasement , The Atlantic charter , Global war , The United Nations , A turbulent peace , An old order gives way , Spaceship Earth , The earth as a global village , Entering the high-tech age , A new millennium , A line , Close call , A sad day , Striking back , A new coin , War in the Middle East, again , A new look at big cities , A Black man becomes the American President , Apologizing , Downturn , China is back , Spring , Friends , An animated chronology.

Misty of Chincoteague (Misty, ,, 1976)
Paul and Maureen Beebe's determination to own a pony from the herd on Chincoteague Island, Virginia, is greatly increased when the elusive Phantom and her colt are among the ponies rounded up for the yearly auction.

Junie B. Jones loves handsome Warren (Junie B. Jones series, 7, 1, 1996)
There’s a new boy in kindergarten, and guess what? He’s the handsomest guy Junie B. has ever seen. She and Lucille and that Grace all want him for a boyfriend. Only, he thinks Junie B. is a nutball. Just ’cause she couldn’t stop laughing and rolling. So how is she supposed to get that boy to love her?

The wizard of Earthsea (Earthsea series, 1, 1, 1975)
The greatest sorcerer in all Earthsea was once a reckless youth, hungry for power and knowledge, who tampered with long-held secrets and loosed a terrible shadow upon the world. This is the tale of his testing, how he mastered the mighty words of power, tamed an ancient dragon, and crossed death's threshold to restore the balance.

The Indian in the cupboard (The Indian in the Cupboard series, 1, 1, 2006)
A nine-year-old boy receives a plastic Indian, a cupboard, and a little key for his birthday and finds himself involved in adventure when the Indian comes to life in the cupboard and befriends him.
Birthday presents , The door is shut , Thirty scalps , The great outdoors , Tommy , The chief is dead, long live the chief , Uninvited brothers , Cowboy! , Shooting match , Breakfast truce , School , Trouble with authority , Art and accusation , The missing key , Underfloor adventure , Brothers.

Saving the sun dragon (Dragon masters, 2, 1, 2014)
The dark magic the dragons encountered in their first adventure has made Ana's sun dragon, Kepri, sick and Drake's earth dragon, Worm, teleports the himself, Kepri, and the four young dragon masters far away from the castle in search of a cure--but the threat of the dark magic still remains.

The BFG (Penguin, Penguin Random House, Distributed by Midwest Tape, Random House, Inc., Listening Library, Scholastic, Penguin Audio, Books on Tape, Puffin Books, an imprint of Penguin Group (USA) Inc, s.n, Knopf, Puffin Books, Farrar, Straus, Giroux, Penguin Young Readers Group, 1998)
The Big Friendly Giant is no ordinary bone-crunching giant. He is far too nice and it's lucky for Sophie that he is. If she had been carried off by any of the other giants she would have been breakfast. When Sophie hears that the giants are headed to England to steal some little children, she and the BFG decide they must stop them once and for all.
The Witching Hour , Who? , The Snatch , The Cave , The BFG , The Giants , The Marvelous Ears , Snozzcumbers , The Bloodbottler , Frobscottle and Whizzpoppers , Journey to Dream Country , Dream-Catching , A Trogglehumper for the Fleshlumpeater , Dreams , The Great Plan , Mixing the Dream , Journey to London , The Palace , The Queen , The Royal Breakfast , The Plan , Capture! , Feeding Time.

Dragon Masters: Rise of the Earth dragon #1 (Dragon masters, 1, 1, 2014)
Eight-year-old Drake is snatched up by the King's soldiers and taken to the castle where he is told by the wizard Griffith that he has been chosen to be a Dragon Master like Ana, Rori, and Bo--and his first task will be to discover whether his dragon, Worm, has any special powers.

The black stallion's courage (Black stallion (Walter Farley), 12, 1, 1984)
In order to raise money to rebuild a one-hundred-thousand-dollar barn, destroyed by fire, Alec returns to racing the Black.